2014
DOI: 10.1186/1556-276x-9-397
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional ribonuclease A-conjugated carbon dot cluster nanosystem for synchronous cancer imaging and therapy

Abstract: Carbon dots exhibit great potential in applications such as molecular imaging and in vivo molecular tracking. However, how to enhance fluorescence intensity of carbon dots has become a great challenge. Herein, we report for the first time a new strategy to synthesize fluorescent carbon dots (C-dots) with high quantum yields by using ribonuclease A (RNase A) as a biomolecular templating agent under microwave irradiation. The synthesized RNase A-conjugated carbon dots (RNase A@C-dots) exhibited quantum yields of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 41 publications
1
38
0
1
Order By: Relevance
“…Yang et al succeeded in using C-dots for the in vivo studies of optical imaging with mice for animal test. Followed by these, as a result of extensive and multidisciplinary efforts, C-dots have found their place in a wide range of applications in nanoprobes [56][57][58][59][60][61][62][63][64][65][66], drug delivery [67][68][69][70][71], therapy [72][73][74][75][76], and optoelectronic devices [77][78][79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al succeeded in using C-dots for the in vivo studies of optical imaging with mice for animal test. Followed by these, as a result of extensive and multidisciplinary efforts, C-dots have found their place in a wide range of applications in nanoprobes [56][57][58][59][60][61][62][63][64][65][66], drug delivery [67][68][69][70][71], therapy [72][73][74][75][76], and optoelectronic devices [77][78][79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…Top-down methods consist of arc discharge [1,5], laser ablation [6][7][8][9], and electrochemical oxidation [10][11][12][13], where the C-dots are formed or "broken off" from a larger carbon structure (such as graphite, carbon rods, graphene Oxides and carbon nanotubes). Bottom-up strategies consist, for example, of combustion/hydrothermal/ acidic oxidation/ultrasonic [14][15][16], supported synthetic [17,18], or microwave methods [19][20][21][22] during which the C-dots are formed from molecular precursors. Meanwhile, the nuance of reaction parameters during synthesis can tremendously affect on the properties of the C-dots, various carbon precursor and synthetic methods.…”
Section: Synthetic Methods Of C-dotsmentioning
confidence: 99%
“…In our group, Liu, et al reported to synthesize fluorescent carbon dots (C-dots) with high quantum yields by using Ribonuclease A (RNaseA) as a stabilizer under microwave irradiation [21]. The preparation process and size, chemical and physical properties of C-dots have been shown in Fig.…”
Section: Synthetic Methods Of C-dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carboxyl groups on the surface of CDs enable them to have excellent water solubility and biocompatibility. In addition, the physical properties of CDs can be enhanced by chemically modifying the surface structure, for example, by applying a 2 Journal of Nanomaterials variety of organic, inorganic, and even biological molecules [5][6][7].…”
Section: Introductionmentioning
confidence: 99%